Fast solution method to prepare hexagonal tellurium nanosheets for optoelectronic and ultrafast photonic applications. Issue 2 (8th December 2020) - Hu, Haiguo; Zeng, Yonghong; Gao, Shan; Wang, Rui; Zhao, Jinlai; You, Kaixi; Song, Yufeng; Xiao, Quanlan; Cao, Rui; Li, Jianqing; Lin, Zhitao; Guo, Jia; et al.
Abstract : High-quality hexagonal Te nanosheets were prepared by a unique solution method and exhibited good optoelectronic and ultrafast photonic properties. Abstract : Tellurene, as a typical non-layered two-dimensional (2D) material, has attracted a lot of attention due to its superior properties such as fast photoconductivity, high thermoelectricity, large piezoelectricity, and excellent nonlinear optical response. Here, a unique, simple, and rapid solution method for the synthesis of high-quality hexagonal Te nanosheets with large area has been proposed. In the presence of polyvinylpyrrolidone (PVP) as a surfactant, the raw material, i.e., tellurium sodium hydride (NaHTe) was rapidly oxidized by O2 in ethanol solution to obtain the hexagonal Te nanosheets with a size of 5–11 μm and a thickness of 50–170 nm. In addition, the experimental results demonstrated that the prepared hexagonal Te nanosheets possessed good optical absorption and exhibited good photoresponse and stability as a photoanode material in a photoelectrochemical (PEC)-type photodetector. Meanwhile, this material also showed excellent nonlinear absorption properties, and the erbium-doped fiber ring laser with the Te nanosheets as a saturated absorption material successfully achieved mode-locking operation at 1550 nm. This work provides new ideas for the preparation of hexagonal Te nanosheets and their applications in optoelectronics and ultrafast photonics.